Fractional Calculus: Models, Algorithms, Technology - Tenreiro Machado, J. A. (2015)
In the last three decades Fractional Calculus (FC) became an area of intenseresearch and development. The accompanying poster illustrates the presentday major achievements in the application of FC in physics, engineeringand biology.